2020
DOI: 10.1111/cen.14272
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids for threatened labour facilitate thyroid maturation among preterm neonates

Abstract: Advances in perinatal care have improved the prognosis for preterm neonates. 1,2 Among them, the administration of antenatal corticosteroids (ANS) is one of the most effective. Since Liggins et al first reported that maternal ANS administration reduced the incidence of neonatal respiratory distress syndrome (RDS) in 1972, 3 its clinical efficacy has been verified in many studies. 4-6 The beneficial effects of ANS have been reported not only in reducing the incidence of RDS, but also in reducing the incidence of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
4
2
0
Order By: Relevance
“…The current study showed that the mean TSH level was 4.36 and 4.24 in both complete and non-ANS courses, in line with our results, the study by Hanaoka et al (2020) showed that the TSH level was 6.2 and 7.6(mIU/L) respectively. They studied a group of 99 very low birth weight neonates (<34 weeks' gestational age) and divided into a complete group (n = 49) whose mothers completed two doses of betamethasone and a group with no ANS (n = 50) who were not exposed to any ANS.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The current study showed that the mean TSH level was 4.36 and 4.24 in both complete and non-ANS courses, in line with our results, the study by Hanaoka et al (2020) showed that the TSH level was 6.2 and 7.6(mIU/L) respectively. They studied a group of 99 very low birth weight neonates (<34 weeks' gestational age) and divided into a complete group (n = 49) whose mothers completed two doses of betamethasone and a group with no ANS (n = 50) who were not exposed to any ANS.…”
Section: Resultssupporting
confidence: 91%
“…On the contrary, Simonetta et al (2007) found that delivery room intubation and respiratory distress syndrome were more frequent in the ANS group and that the length of stay was also significantly longer in this group. Also, this comes in agreement with Hanaoka et al, (2020) who found that the ANS group needed less resuscitation and less servant administration.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations